AN ANALYSIS OF THE FACTORS OF STUDENT’S DIFFICULTIES IN READING COMPREHENSION AT VIII (G) GRADE AT SMP N 30 SEMARANG - Yustika Ratri Ningrum; T Sri Suwarti; Ajeng Setyorini (Edelweiss : Journal Of Innovation In Educational Research, 2024)
Reading take a very important role in contributing students background knowledge to speak and to write. However, many students still have difficulties in understanding the words, comprehending the reading text, making inference, determining main idea, and locating reference.The objective of this research is to find outstudents’ difficulties in comprehending reading text and what strategiesused to overcome the difficulties. This research was a qualitative research and used descriptive method to expose the data which was collected by questionnaire and analyzed using Likert scale.The sample was the third year students of SMPN 30 Semarang. The questionnaire consisted of 15 statements related to their opinion on difficulties in comprehending reading text. Other 20 statements related to their strategies in overcoming the difficulties namely metacognitive and cognitive.The data revealed that 75% of the students had strong and 5,6% students had very strong comprehension. This meant that the students had good orvery good reading comprehension ability but some students still got difficulties. Besides, there were 2, 8% of the students had weak comprehension and 16, 6% had average level of comprehension or had a bit of difficulties. In using the two strategies, the students had Average criterion (55,5%). They mostly tended to use metacognitive strategies (78%) in reading comprehension